XIX. asır başlarına kadar Osmanlı Devleti’ nde Şeyhu’ l İslamlık - Akgündüz, Murat (My University, 1999)
My thesis which research the office of Şeyhu'l-İslam in the Ottoman State until the begining of XIX. century is constituded an introduction and six chapter. In Introduction, after informing researchs and basic books wich are connected with theme, has been summarized the Learning Organization of the Ottoman State. Afterwards was researched that how arise the term of Şeyhu'l-İslam and scholars whose are remembered this nickname in the other Islamic countries. In first chapter which is researched the development phases of the office of Şeyhu'l-İslam in Ottoman State, first of all has been critisized the opinions which are adduced about the foundation date and emphasized that the arise of the office of Şeyhu'l-İslam as the head of learning and religion authority in the second half of XVI. century. After the phase of foundation, has been summarized the biographies of the famous Şeyhu'l-İslam's whose work in the rise and regression periods. At the end of first chapter, has been explained that the office of Şeyhu'l-İslam is carried to the centre of Yeniçeri at the date of 1242/ 1826. In the following chapters, has been touched on the place and importance of the office of Şeyhu'l-İslam in state organization, how appointment and dismissal the Şeyhu'l-İslam's. In the fifth chapter has been explained the officers Fetva Emîni, Kethüda, Telhisçi whose work in the office of Şeyhu'l-İslam and the sources of profit. In the sixth chapter has been researched the duties of Şeyhu'l-İslam under four tittle. First of all the duties of Şeyhu'l-İslam in the law area was branched as the pay of fetva, the control of Kânunnâme and administration of some foundations. After the duties of Şeyhu'l-İslam in the learning and education area was branched in the same way as inferior tittles. For example, the duties of Şeyhu'l-İslam in the appointment and dismissal of the learning officer has been explained depended on the archive documents. The duties of Şeyhu'l-İslam in the religious affairs was branched as the appointment and dismissal of the officers imam-hatib, müezzin, vâiz whose work in the mosques and the şeyhs whose are founded in the dervish lodges. Finally was touched on the activity of Şeyhu'l-İslam in the political and administratif area as the declaration of war and the affirm of treaty.
Keywords: OSMANLI İMPARATORLUĞU; ŞEYHU’L-İSLAMLIK